A Problem of Ancient Topography: Lachish and Eglon - Wright, G. Ernest
reprinted from HThR 64 (1971); with Appendix by Lawrence E. Stager, Climatic Conditions and Grain Storage (at Tell el-Hesi) in the Persian Period: 86-88, 1 fig.